Polityczna siła kina. Bollywood jako „soft power” Indii - Wasiłek, Bartosz (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
Films are very important in the socialization process and in all social relations. Based on this observation the author shows the usefulness of movies as a tool of foreign policy. Undoubtedly the popular culture of the United States dominated the world. However the international situation changes. The new powers are growing and they will no longer passively accept American culture. They want to show to the world their own values and their own point of view. India was the first to realize the power of soft power and decided to fight with America for the love of people. India started to promote their culture all over the world using Bollywood movies.